System Quality and Service Quality in Public Sector Accounting Information Systems: The Role of Perceived Usefulness in Enhancing User Satisfaction - Tri Lestari; Sri Rahayu; Achmad Hizazi; Wirmie Eka Putra (Greenation International Journal of Economics and Accounting, 2026)
This study is motivated by the suboptimal level of user satisfaction in public sector accounting information systems. It aims to examine the effect of system quality and service quality on user satisfaction with the mediating role of perceived usefulness. The research object consists of work units partnering with the State Treasury Service Office in Jambi, with 161 respondents. The study applies a quantitative approach using a survey method and structural equation modeling analysis. The results show that system quality and service quality have a positive and significant effect on perceived usefulness. Perceived usefulness has a positive and significant effect on user satisfaction. Service quality also has a direct effect on user satisfaction, while system quality has no direct effect. Perceived usefulness fully mediates the relationship between system quality and user satisfaction and partially mediates the relationship between service quality and user satisfaction. Overall, respondents perceive the variables at a high level. The findings refine the integration of the Information System Success Model and the Technology Acceptance Model by demonstrating that perceived usefulness serves as the primary mechanism through which system quality influences user satisfaction in mandatory system environments. This study concludes that enhancing perceived usefulness is essential to improving user satisfaction.